Vascular Endothelial Growth Factor-Capturing Aligned Electrospun Polycaprolactone/Gelatin Nanofibers Promote Patellar Ligament Regeneration. (1st March 2022) - Yuan, Zhengchao; Sheng, Dandan; Jiang, Liping; Shafiq, Muhammad; Khan, Atta ur Rehman; Hashim, Rashida; Chen, Yujie; Li, Baojie; Xie, Xianrui; Chen, Jun; Morsi, Yosry; Mo, Xiumei; et al.
Abstract: Ligament injuries are common in sports and other rigorous activities. It is a great challenge to achieve ligament regeneration after an injury due the avascular structure and low self-renewal capability. Herein, we developed vascular endothelial growth factor (VEGF)-binding aligned electrospun poly(caprolactone)/gelatin (PCL/Gel) scaffolds by incorporating prominin-1-binding peptide (BP) sequence and exploited them for patellar ligament regeneration. The adsorption of BP onto scaffolds was discerned by various techniques, such as Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, and confocal laser scanning microscope. The accumulation of VEGF onto scaffolds correlated with the concentration of the peptide in vitro . BP-anchored PCL/Gel scaffolds (BP@PCL/Gel) promoted the tubular formation of human umbilical vein endothelial cells (HUVECs) and wound healing in vitro . Besides, BP containing scaffolds exhibited higher content of CD31 + cells than that of the control scaffolds at 1 week after implantation in vivo . Moreover, BP containing scaffolds improved biomechanical properties and facilitated the regeneration of matured collagen in patellar ligament 4 weeks after implantation in mice. Overall, this strategy of peptide-mediated orchestration of VEGF provides an enticing platform for the ligament regeneration, which may also have broad implications for tissue repair applications. Statement of significance: Ligament injuries are central to sports and other rigorous activities. Given to the avascular nature and poor self-healing capability of injured ligament tissues, it is a burgeoning challenge to fabricate tissue-engineered scaffolds for ligament reconstruction. Vascular endothelial growth factor (VEGF) is pivotal to the neo-vessel formation. However, the high molecular weight of VEGF as well as its short half-life in vitro and in vivo limits its therapeutic potential. To circumvent these limitations, herein, we functionalized aligned electrospun polycaprolactone/gelatin (PCL/Gel)-based scaffolds with VEGF-binding peptide (BP) and assessed their biocompatibility and performance in vitro and in vivo . BP-modified scaffolds accumulated VEGF, improved tube formation of HUVECs, and induced wound healing in vitro, which may have broad implications for regenerative medicine and tissue engineering. Graphical abstract: Image, graphical abstract